Environmental Policy Instruments for Investments in Backstop Technologies Under Present Bias - An Application to the Building Sector - Fabian Arnold; Amir Ashour Novirdoust; Philipp Theile (Environmental and Resource Economics, 2025)
Governments worldwide have set targets to reduce greenhouse gas emissions from the residential sector to zero or close to zero. Policy instruments, such as carbon pricing or subsidies, are being discussed and implemented to achieve these targets. If individuals exhibit present bias, Heutel ( 2015 ) has shown that optimal policies targeting investments in externality-producing durable goods consist of two components, one aimed at the externality and one aimed at the present bias. We generalize Heutel's theoretical model by defining a larger technology set. This allows us to represent the dependence of fuel prices and emission intensities on technologies used to include a zero-emission backstop technology. We examine the implications of this model generalization, and we numerically assess the effect in a stylized case study for a representative building in Germany. We show that as long as social costs of carbon and the corresponding price are not high enough to make the backstop technology optimal, Heutel's proposition holds that optimal policies must consist of two components. Generalizing Heutel's proposition, a single instrument can address present bias, if the social costs of carbon and the price are high enough. While the level of this single instrument, i.e., a tax or subsidy, depends on the level of present bias, we find that there exists a tax-subsidy combination that is optimal regardless of the level of present bias.
Keywords: D15:D62; D91; H23; Q48; Q58; 330; Present bias; Policy; Heating investments; Durable goods; Climate neutrality